2021
DOI: 10.3390/healthcare9121627
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Knowledge and Perception among the Healthcare Workers during the COVID-19 Pandemic in Qassim, Saudi Arabia: A Cross-Sectional Survey

Abstract: Hand hygiene is among the most important factors of infection control in healthcare settings. Healthcare workers are the primary source of hospital-acquired infection. We assessed the current state of hand hygiene knowledge, perception, and practice among the healthcare workers in Qassim, Saudi Arabia. In this cross-sectional study, we used the hand hygiene knowledge and perception questionnaire developed by the World Health Organization. Knowledge and perceptions were classified into good (80–100%), moderate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 20 publications
(24 reference statements)
3
18
2
Order By: Relevance
“…This, however, is in contrast with their knowledge that a minimum of 20 seconds is required to remove most microbes from the hand. The perception related to HCAI’s reported in the current study compares favourably with that reported for HCW’s in Saudi-Arabia (2021) 48 where 95.4% perceived HH to be effective against HCAI’s. Following on from the discussion of how long to use an ABHR and also if hand rubbing or hand washing would be the correct HH practice, the response to the question of if the individual used ABHR regularly is appropriate.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This, however, is in contrast with their knowledge that a minimum of 20 seconds is required to remove most microbes from the hand. The perception related to HCAI’s reported in the current study compares favourably with that reported for HCW’s in Saudi-Arabia (2021) 48 where 95.4% perceived HH to be effective against HCAI’s. Following on from the discussion of how long to use an ABHR and also if hand rubbing or hand washing would be the correct HH practice, the response to the question of if the individual used ABHR regularly is appropriate.…”
Section: Discussionsupporting
confidence: 68%
“…This would classify as moderate HH knowledge, which when compared with other research studies are fairly similar. Hand hygiene knowledge during COVID-19 in Saudi-Arabia 48 was reported as moderate at 57.8%, and moderate among under-graduate students in India at 69.1%. 49 One would have expected that HH knowledge should have been higher for the 2022 group due to their exposure in the COVID-19 pandemic, but it was not the case.…”
Section: Discussionmentioning
confidence: 93%
“…A structured questionnaire that was adapted from WHO guidelines and published papers [34,[36][37][38] and contextualized based on the study setting. The questionnaire was prepared in English, translated to the local language (Amharic), and then re-translated to the English language for consistency.…”
Section: Data Collection Tools and Quality Assurancementioning
confidence: 99%
“…Hand hygiene has been one of the most important factors of infection control in a healthcare setting, according to a cross-sectional survey in Saudi Arabia. The hand hygiene knowledge and perception of the HCWs showed that the majority had moderate knowledge (57.8%) with perception (73.4%) of hand hygiene ( 8 ). The HCWs who were trained on hand hygiene were more likely to have good/ moderate perceptions than those without training.…”
Section: Introductionmentioning
confidence: 99%